World Christianity 2026: Anticipating the Future - Zurlo, Gina A. (International bulletin of mission research, 2026)
This article represents the 42nd year of providing annual statistics in the International Bulletin of Mission Research. This year’s article highlights new future projections to the year 2075. Major findings of the 2075 data include the continuation of Christianity’s shift to the Global South, the increased importance of Christian-Muslim relations in light of the latter’s increasing share of the world’s population, and the Demographic Republic of the Congo eventually replacing the United States as the country with the most Christians in the world.